Combination phentermine and topiramate for weight maintenance: the first Australian experience. Issue 4 (18th August 2014) - Neoh, Sandra L; Sumithran, Priya; Haywood, Cilla J; Houlihan, Christine A; Lee, Fiona T H; Proietto, Joseph
Abstract: Objective: To investigate the safety, tolerability and efficacy of combination phentermine and topiramate therapy for maintenance of weight loss. Design, setting and patients : Retrospective audit of patients attending the Austin Health Weight Control Clinic who were dispensed phentermine–topiramate between 22 January 2010 and 16 July 2012 and after reaching a target weight by following a very low energy diet (VLED). Data collection continued until July 2013. Main outcome measures: Number of patients who ceased pharmacotherapy; duration of use of pharmacotherapy; types and numbers of adverse effects; and mean weight and blood pressure measurements at the initial visit, the end of the VLED and the last observation during pharmacotherapy. Results: Data were available for 103 patients who were dispensed phentermine–topiramate; 61 patients ceased combination pharmacotherapy before the end of the data collection period, 41 due to adverse effects (eg, paraesthesia, cognitive changes, dry mouth and depression). The mean duration of use of pharmacotherapy was 10 months. Mean weight decreased by 10% due to the VLED (from 135.5 kg to 122.5 kg) and this loss was maintained. For 30 patients who continued on phentermine–topiramate, the mean duration of pharmacotherapy was 22 months and the mean weight decreased by 6.7 kg between the end of the VLED and the last observation during pharmacotherapy. Conclusion : Phentermine–topiramate therapy was not well tolerated; more than half of the patients in our study stopped taking it because of adverse effects, and more than half of the adverse events reported were ascribed to topiramate. However, in those able to continue with pharmacotherapy, the combination was efficacious for both maintenance of weight loss and ongoing weight loss.